Effect of green tea and mulberry leaf powders on the gut microbiota of chicken - Yuan Chen; Jiajia Ni; Hongwei Li (BMC Veterinary Research, 2019)
Abstract Background The gut microbiota is closely correlated with host health and is strongly influenced by food composition. Chinese herbs are usually used as natural feed additives in livestock production. Therefore, the present study assessed the influence of diet supplementation with green tea and mulberry leaf powders on the chicken gut microbiota. The gut microbiota compositions were determined using 16S rDNA sequencing. Results Enhanced relative abundances of Bacteroides, Prevotella, and Megamonas were found in the chicken gut when mulberry leaf powder was added to diet. Conversely, a higher abundance of potentially pathogenic Gallibacterium was found in the chicken gut when the diet was supplemented with green tea powder. These results indicated that green tea powder and mulberry leaf powder can greatly affect the gut microbiota of chickens by changing their compositions. Conclusions It is imperative to examine and evaluate the effects of Chinese herbs on animal health before they are introduced as feed additives in animal production.